Post-exercise Recovery Methods Focus on Young Soccer Players: A Systematic Review - Calleja-González, Julio; Mielgo-Ayuso, Juan; Miguel-Ortega, Álvaro; Marqués-Jiménez, Diego; Del Valle, Miguel; Ostojic, Sergej M.; Sampaio, Jaime; Terrados, Nicolás; Refoyo, Ignacio (Frontiers in Physiology, 2021)
Background: Prescription of post-match or post-training recovery strategies in young soccer players is a key point to optimize soccer performance. Considering that the effectiveness of recovery strategies may present interindividual variability, scientific evidence-based recovery methods and protocols used in adults are possibly not applicable to young soccer players. Therefore, the current systematic review primarily aimed to present a critical appraisal and summary of the original research articles that have evaluated the effectiveness of recovery strategies in young male soccer players and to provide sufficient knowledge regarding the effectiveness of the recovery methods and strategies. Methodology: A structured search was carried out following the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines until November 31, 2020, using the next data bases: WOS, PubMed, Cochrane Library, Evidence Database (PEDro), Evidence Based Medicine (EBM) Search review, EMBASE, and Scopus. There were no filters applied. Results: A total of 638 articles were obtained in the initial search. After the inclusion and exclusion criteria, the final sample was 10 articles focusing on recovery in young male players. Conclusions: Neuromuscular performance can be recovered using WVB but not with SS, and water immersion protocols may also be useful, but their positive effects are not significant, and it is unable to distinguish the best water immersion method; match running performance maintenance may be achieved using water immersion protocols but no other recovery methods have been investigated; EIMD and inflammatory responses could be positively affected when water immersion and AR are applied, although SS seems to be ineffective; perceptual responses also seem to be better with CWI and WVB, but contradictory results have been found when AR is applied, and SS had no positive impact. Finally, it is important to consider that AR strategies may modify HR response and soccer-specific performance.